Ligninolytic activity from newly isolated basidiomycete strains and effect of these enzymes on the azo dye orange II decolourisation - Abrahão, Maira Cortellini [UNESP]; Gugliotta, Adriana de Mello; Da Silva, Roberto [UNESP]; Yashihiro Fujieda, Roberto Joanne [UNESP]; Boscolo, Mauricio [UNESP]; Gomes, Eleni [UNESP] (Springer, 2008)
Wood-rotting fungi have the ability to degrade lignin by secreting ligninases, a promising enzyme for degradation of environmental pollutants. Nine basidiomycete strains collected just outside the city of Sao Jose do Rio Preto, upstate São Paulo, Brazil, were evaluated for their manganese peroxidase (MnP), lignin peroxidase (LiP) and laccase production by solid-state fermentation on wheat bran. Datronia caperata SP381992, Polyporus tenuiculus SP381977 and Pycnoporus sanguineus SP381968 were the highest producers of laccase, while Polyporus tenuiculus SP381971, Datronia caperata SP381992, Coriolopsis polyzona SP381989 and Hexagonia hirta SP382026 produced the most MnP and UP activity. The majority of strains secreted laccase with optimum activity at 70 C and, when maintained at 60 C, in the absence of substrate, the crude enzymes preserved 100% of their initial activity for periods of 30 min up to 8 h. Enzymes from D. caperata SP381992, P. tenuiculus SP381977, P. sanguineus SP381968 and H. hirta SP382026 were tested for activity on the azo dye orange II and afforded 96-100% decolourisation of the dye in 1 to 48 h. Since this reaction depended on the presence of ABTS and there was no decolourisation when H(2)O(2) or MnSO(4) was present, it was attributed to the laccase activity.
Keywords: Ligninases; Basidiomycetes; azo dye; orange II